Psychological analysis of handwriting as a subject of forensic psychological examination - Makhmudova Hulkar Tilabovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the actual possibilities of psychological analysis of handwriting, taking into account modern scientific approaches. The significance of this area for law enforcement agencies is associated with the study of various handwritten texts, including the psychological analysis of the suicide note of a possible suicide. The use of psychological analysis of handwriting by forensic psychologists will allow diagnosing, predicting and conducting objective psychological expert research within the framework of the questions posed.